2012
DOI: 10.1016/j.tplants.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

From thin to thick: major transitions during stem development

Abstract: The variability of shoot architecture in plants is striking and one of the most extreme examples of adaptive growth in higher organisms. Mediated by the differential activity of apical and lateral meristems, flexibility in stem growth essentially contributes to this variability. In spite of this importance, the regulation of major events in stem development is largely unexplored. Recently, however, novel approaches exploiting knowledge from root and leaf development are starting to shed light on molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 98 publications
3
64
0
Order By: Relevance
“…The Class III HOMEODOMAIN LEUCINE-ZIPPER (HD-ZIP III) transcription factors have emerged as important regulators of vasculature organization and polarity in the shoot, as in the root and hypocotyl (reviewed by Sanchez et al, 2012). As mentioned above, Arabidopsis has five HD-ZIP III genes: REVOLUTA (REV/ IFL), PHABULOSA (PHB/ATHB14), PHAVOLUTA (PHV/ATHB9), CORONA (CNA/ATHB15) and ATHB8.…”
Section: Transcription Factor Mediated Regulation Of Cambial Developmmentioning
confidence: 99%
“…The Class III HOMEODOMAIN LEUCINE-ZIPPER (HD-ZIP III) transcription factors have emerged as important regulators of vasculature organization and polarity in the shoot, as in the root and hypocotyl (reviewed by Sanchez et al, 2012). As mentioned above, Arabidopsis has five HD-ZIP III genes: REVOLUTA (REV/ IFL), PHABULOSA (PHB/ATHB14), PHAVOLUTA (PHV/ATHB9), CORONA (CNA/ATHB15) and ATHB8.…”
Section: Transcription Factor Mediated Regulation Of Cambial Developmmentioning
confidence: 99%
“…The vascular cambium, from which all secondary xylem and phloem tissues arise during secondary growth, develops from the procambium and interfascicular parenchyma (Plomion et al, 2001; Baucher et al, 2007). As per the convention of Dettmer et al (2009), we generally refer to procambiums and (secondary) vascular cambiums as vascular meristems, which are thought to be regulated in a similar, but not identical, fashion to shoot and root apical meristems (Sanchez et al, 2012; Milhinhos and Miguel, 2013) (Figure 1). …”
Section: Vascular Patterning and Differentiationmentioning
confidence: 99%
“…BP, ATHB18, a C2H2-type zinc finger protein At3g46080, MYB20, MYB69, MYB79, MYB85, and the functionally redundant pair MYB58/MYB63 are known only to directly or indirectly regulate lignin biosynthetic genes (Mele et al, 2003; Zhou et al, 2009; Mitsuda et al, 2010), whereas BES1 is the only TF currently shown to bind to cellulose synthase ( CesA ) genes in both primary and SCWs (Xie et al, 2011) (Figures 1, 2). BP is a KNOX gene family member that maintains shoot apical meristems (Sanchez et al, 2012) and strongly represses lignification in inflorescence stems (Mele et al, 2003). MYB85 appears to specifically regulate the lignin pathway (Zhong et al, 2008a) and appears to be regulated by MYB46/MYB83 (Figure 1, Additional file 1).…”
Section: The Scw Transcriptional Network: Structure Evolution and Dmentioning
confidence: 99%
“…Dicotyledonous plants have the vascular cambium and produce a ring of vasculature, known as a eustele, with the xylem on the inside and phloem on the outside. Monocots lack the vascular cambium and instead have what is referred to as a scattered venation pattern (or atactostele) (Sanchez et al, 2012). Monocots and dicots also differ in how veins enter from leaves into stems.…”
Section: Introductionmentioning
confidence: 99%